Perumusan Strategi Pemasaran Menggunakan Metode Analisis SWOT - Steven Andeas; Agustian Suseno (Peneliti.net, 2022)
Strategy management is one of the aspects that is very important to support marketing in terms of implementing marketing strategies in one company because of the emergence of new companies that certainly have their own advantages and disadvantages. This leads to a very intense competition where new companies today have the advantage to maintain their existence in a competition. This phenomenon makes changes in consumer behavior that was more product quality oriented to be oriented to low price. PT. Koolzone Indonesia is one of the companies engaged in the distribution of goods or commonly referred to as distributors, goods distributed by PT. Koolzone Indonesia is Freezer and Chiller and PT. Koolzone Indonesia definitely needs a proper business strategy so that it can be the main choice for consumers. The purpose of this study is to formulate the most appropriate strategies used to increase competition by using SWOT Analysis by identifying internal factors namely strength and weakness and external factors, namely opportunities and threats in the PT. Koolzone Indonesia’s environment.